CHARAKTERISTICS OF BALI CATTLE YOUNG BULL UNDER TRADITIONALLY LIVESTOCK SYSTEM IN MERBAUN VILLAGE REGENCY OF KUPANG - Baharun, Abdullah; L. L Belli, Henderiana; Hine, Thomas M (Jurnal Peternakan Nusantara, 2017)
An experiment had been conducted in Merbaun Village, Regency of Kupang for three months. The objective of the experiment was to know characteristics of Bali cattle Bull i.e. age and body weight, body score condition, linier body size (e.g. chest girth, body length, and shoulder height), libido, scrotum circumference, and semen production. 125 of Bali cattle Bull with aged about 2-2,5 years were used  in physical measured while nine Bull were choosen randomly to measure libido and semen production. The results of the experiment showed that the average age and body weight were 25.83 ± 0.3719 months and 207.37 ± 1.84 kg, with BCS of 3.97 ± 0.04  (from 5 score), and the chest girth, body length, and shoulder height were 158.27 ± 0.71 cm, 106.87 ± 0.26 cm, and 108.55 ± 0.37 cm, respectively. About 77 head (61.6%) was brown colour, and the other 48 (38.4%) was black, with moderate of capacity of libido (score 7.22 ± 0.66  from  9 score). The average of scrotum circumference was 25.67±1.20 cm, volume of semen were  2.54±0.69 ml and sperm concentration was 1.26 x 109 per ml repectively. Of the total of 125 Bali cattle young bull, only 26% fulfilled the Indonesia Standard of Bali young bull.Key word : young bull, bali cattel, traditionally livestock.